Purification of microbial exo-polylaacturonase by different techniques (Research, Society and Development, 2021)
The demand for enzyme and protein purification processes has been increasing, mainly due to the search on the part of industries for products with a high degree of purity. The transformation with non-ionic polymers, solvents and salts may be necessary in the purification of enzymes, such as polygalacturonase, used mainly in the production of wines, juices, processed foods such as infant foods, without resulting in yield losses. In this context, the objective of the present work was to evaluate the efficiency of different techniques of enzymatic concentration (pre-purification). Reconstruction with acetone and ethanol solvents was performed in tools of 1, 2 and 3V, for ammonium sulphate were used from 0-80%, with intervals of 20%. According to the results of the partial purification of polygalacturonase (PG), it was observed that the highest enzyme recoveries were added at a solvent concentration of 3V for ethanol and 2V for acetone with values of 47,05% and 42,85% respectively.